America alone : the neo-conservatives and the global order - Halper, Stefan A. (Cambridge University Press, 2004)
This book explores how George W. Bush's election, and the fear and confusion of September 11, combined to allow a small group of radical intellectuals to seize the reins of U.S. national security policy. At this 'inflection point' in U.S. history, an inexperienced president was persuaded to abandon his campaign pledges (and the successful consensus-driven, bi-partisan diplomacy that managed the lethal Soviet threat over the past half-century) and adopt a neo-conservative foreign policy emphasizing military confrontation and 'nation-building'. To date, the costs--in blood, money and credibility--have been great and the benefits few, with traditional conservatives deploring Bush's approach. The book sets out an alternative approach emphasizing the traditional conservative principles of containing risk, consensus diplomacy and balance of power. Features: the first in-depth coverage of people controlling American foreign policy; how the Iraq War cost America blood, money, and credibility abroad and reduced freedom at home--yet, beyond toppling Saddam Hussein, brought few benefits; how neo-conservatives hijacked the war on terrorism for their own purposes; what's at stake for America internationally and why policy changes are necessary.